2016
DOI: 10.1038/srep25284
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Corrigendum: Tomato yellow leaf curl virus infection mitigates the heat stress response of plants grown at high temperatures

Abstract: Scientific Reports 6: Article number: 19715; Published online: 21 January 2016; Updated: 11 May 2016 The original version of this Article contained errors in the spelling of the authors Ghandi Anfoka, Adi Moshe, Lilia Fridman, Linoy Amrani, Or Rotem, Mikhail Kolot, Mouhammad Zeidan, Henryk Czosnek and Rena Gorovits which were incorrectly given as Anfoka Ghandi, Moshe Adi, Fridman Lilia, Amrani Linoy, Rotem Or, Kolot Mikhail, Zeidan Mouhammad, Czosnek Henryk and Gorovits Rena respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Indeed, TYLCV-infected tomatoes are characterized by low levels of cell death; moreover, TYLCV is able to alleviate cell death, induced by the other stresses such as heat (Anfoka et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, TYLCV-infected tomatoes are characterized by low levels of cell death; moreover, TYLCV is able to alleviate cell death, induced by the other stresses such as heat (Anfoka et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that heat stress and TYLCV infection can induce similar responses in plants (Clarke et al, 2004, 2009; Anfoka et al, 2016; Li et al, 2017). Since TYLCTHV is one of the predominant begomoviruses infecting tomato in Taiwan, tomato plants were infected with TYLCTHV to verify the similarity between plant responses to heat stress and viral disease.…”
Section: Resultsmentioning
confidence: 99%
“…After TYLCTHV infection, anise oil and eugenol decreased the expression of AC1 and BC1 compared to the control (Figures 3E,F). Moreover, heat stress has been demonstrated to enhance accumulation of TYLCV (Anfoka et al, 2016). Anise oil and eugenol also decreased the expression of AC1 and BC1 compared to the control after TYLCTHV infection combined with heat treatment (Figures 3E,F).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations